2003
DOI: 10.1111/j.0906-6705.2003.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Hair follicle dermal cells differentiate into adipogenic and osteogenic lineages

Abstract: The adult hair follicle dermal papilla (DP) and dermal sheath (DS) cells are developmentally active cell populations with a proven role in adult hair follicle-cycling activity and unique inductive powers. In stem cell biology, the hair follicle epithelium has recently been the subject of a great deal of investigation, but up to now, the follicle dermis has been largely overlooked as a source of stem cells. Following the sporadic appearance of muscle, lipid and bone-type cells in discretely isolated follicle DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
213
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(229 citation statements)
references
References 60 publications
11
213
0
5
Order By: Relevance
“…Even more important, HFCs displayed multipotency as they differentiated toward fat, bone, cartilage, and SMCs, suggesting that these cells may be very similar to MSCs derived from the BM, adipose, or other tissues. Two previous studies showed that rat hair follicle cells exhibited tri-lineage differentiation potential, 7,8 but this is the first report to show that human HFCs exhibit similar properties. Although we recently showed that ovine hair follicle cells contained functional and contractile SMCs, 9 they failed to differentiate toward osteogenic, adipogenic, or chondrogenic lineages (our data not shown), suggesting that interspecies differences may be significant.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Even more important, HFCs displayed multipotency as they differentiated toward fat, bone, cartilage, and SMCs, suggesting that these cells may be very similar to MSCs derived from the BM, adipose, or other tissues. Two previous studies showed that rat hair follicle cells exhibited tri-lineage differentiation potential, 7,8 but this is the first report to show that human HFCs exhibit similar properties. Although we recently showed that ovine hair follicle cells contained functional and contractile SMCs, 9 they failed to differentiate toward osteogenic, adipogenic, or chondrogenic lineages (our data not shown), suggesting that interspecies differences may be significant.…”
Section: Discussionmentioning
confidence: 69%
“…[21][22][23][24][25] Comparison between fibroblasts from interfollicular skin and hair follicles prompted some investigators to suggest that the niche of skin multipotent stem cells resides in the hair follicle. 7,26,27 Indeed, two recent studies confirmed the multipotent nature of rat hair follicle cells and showed similar differentiation potential to BM-MSCs. 7,8 Our results extent these findings to the human system and confirm that our isolation protocol renders cells from human hair follicles with the potential to differentiate toward osteogenic, adipogenic, chondrogenic, and myogenic lineage.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…As a control, both human infant and newborn rat SKPs were maintained for several passages in liquid media dermosphere culture (Fig. 2B), as expected [21,22,24,25,27,35].…”
Section: In Vitro Passage Of Human Skin-derived Precursor (Skp) Cellsmentioning
confidence: 81%